Labor Productivity Convergence in Indonesia: Spatially Dynamic Panel Data Analysis - Ahmad Fajar Novianto; Waris Marsisno (EKO-REGIONAL, 2019)
The problem of labor productivity in Indonesia is a regional and sectoral inequality. To know the time required to remove inequality, can be measured by the level of convergence of labor productivity. The research would analyze the rate of sectoral labor productivity convergence among provinces in Indonesia spatially and identify the determinant factors of labor productivity. The analytical methods used is spatial dinamic panel data with Spatially Corrected Blundell-Bond (SCBB) estimation method. The results show that there are spatially sectoral labor productivity convergence. Primary sector takes the longest half-life convergence of 7-8 years, while secondary takes 1-2 years and tertiary sector takes 3-4 years. Furthermore, the Gross Capital Fixed Formation, Mean Years of Schooling, and real wage sectoral are significantly have positive affect to the labor productivity while Life Expectancy is significantly have negative affect to labor productivity.Keywords : convergence, spatial analysis, labor productivity